Le rapport au temps dans le travail enseignant - Tourneville, Julien (de Bordeaux, 2021)
With the injunction to adapt, innovate, multiply team projects and differentiate teaching, a dominant professionality is taking shape that demands ever greater professional involvement and that dictates the time of teachers. In so doing, it conflicts with the process of professionalization that has been characteristic of teaching since the 1980s, and leads to a series of phenomena that can result in the effects of deprofessionalization among teachers: loss of autonomy, short-term vision, and loss of meaning. This thesis proposes to take stock of the dialectic of professionalization/deprofessionalization in the field of teaching through the prism of lived time. Thus, the results will seek to reveal the effects of deprofessionalization.